2012
DOI: 10.3109/03008207.2012.712583
|View full text |Cite
|
Sign up to set email alerts
|

Agarose Gel as Biomaterial or Scaffold for Implantation Surgery: Characterization, Histological and Histomorphometric Study on Soft Tissue Response

Abstract: Maxillofacial, orthopedic, oral, and plastic surgery require materials for tissue augmentation, guided regeneration, and tissue engineering approaches. In this study, the aim was to develop and characterize a new extrudable hydrogel, based on agarose gel (AG; 1.5% wt) and to evaluate the local effects after subcutaneous implantation in comparison with collagen and hyaluronic acid. AG chemical-physical properties were ascertained through Fourier transform infrared (FT-IR) spectroscopy and rheological analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Furthermore, a recent investigation reported that agarose implanted in rats does degrade as a result of phagocytosis, suggesting that lack of biodegradability may not be a significant concern. 72 This study represents a major advance in our effort to engineer functional, articular surface-sized cartilage constructs for the resurfacing of OA joints. From our perspective, the remaining challenges include (a) the need to reach native levels of collagen content, enhance interstitial fluid pressurization, and produce dynamic compressive moduli and friction coefficients that match native values;…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent investigation reported that agarose implanted in rats does degrade as a result of phagocytosis, suggesting that lack of biodegradability may not be a significant concern. 72 This study represents a major advance in our effort to engineer functional, articular surface-sized cartilage constructs for the resurfacing of OA joints. From our perspective, the remaining challenges include (a) the need to reach native levels of collagen content, enhance interstitial fluid pressurization, and produce dynamic compressive moduli and friction coefficients that match native values;…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the physical structure of the gels can be altered by varying the agarose concentration which results in desired pore sizes. Therefore agarose based hydrogel scaffolds [58] and composite scaffolds made of agarose combined with HAp [59] finds its applications in bone tissue engineering.…”
Section: Agarosementioning
confidence: 99%
“…However, like other implantable materials, hydrogels based on collagen, 101,102 hyaluronic acid, 101 agarose, 101 polyethylene glycol, 103 and alginates 104 generally elicit an innate immune response in the form of robust infiltration of neutrophils into the surrounding tissue, with subsequent encapsulation. Exceptions to this phenomenon are rare in the literature, but some cross-linked polyethers have been shown to have mild innate immune responses.…”
Section: Implanted Devices and Atpmentioning
confidence: 99%